Waste management system using RFID and ultrasonic sensor - Rahman, Md. Mafiur; Das, Nejhum Kanti; Rahat, Fardin Rizvy; Alif, Shamsul Arefin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.